Culturally Diverse Patient Experiences and Walking Interviews: A Co-Design Approach to Improving Organizational Health Literacy - Lloyd, Jane (Health Lit Res Pract, 2019)
People from diverse cultural and linguistic backgrounds are more likely to have low health literacy and less appropriate access to health services than other Australians. Interventions to improve health literacy have demonstrated moderate improvements in health service use. Most of these interventions focus on simplifying communication as opposed to navigation support. A comprehensive and multilevel response is required if the health care system and organizations are to be more responsive to different levels of health literacy. This includes obtaining feedback from patients on their experience of accessing health care. This study piloted the use of a co-design process to develop a culturally appropriate mechanism of elucidating the perspectives of community members of culturally diverse groups on their experiences of accessing a health service to identify the strengths and weaknesses of an organization's health literacy. This co-design process involved the adaptation of an existing “Walking Interview” tool to the location and language groups being targeted, as well as determining the process for recruiting participants and conducting the walking interviews. The interviews provided valuable insights into the experiences of culturally diverse groups in accessing Canterbury Hospital and identified areas for improvement, such as clearer signage and access to interpreter services. [HLRP: Health Literacy Research and Practice. 2019;3(4):e238–e242.]